Gaya Kepemimpinan Situasional Perempuan di Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Surabaya - Cindy Lestari; Yuni Lestari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Women’s leadership refers to women’s active participation in strategic roles within government agencies. This study was motivated by the phenomenon of women’s leadership at the Surabaya City BKPSDM, specifically focusing on one of the female task force leaders who demonstrated situational leadership through a flexible, communicative approach that involved employees in the work process. This study aims to analyze the situational leadership style applied by the female leader at the BKPSDM of Surabaya City. The research focus is directed at the application of situational leadership styles based on Hersey and Blanchard’s theory, which encompasses four indicators: Telling, Selling, Participating, and Delegating. This study employs a descriptive qualitative research method. Data collection was conducted through interviews, observations, and documentation. The research findings indicate that the application of situational leadership by the head of the XX Division work team was quite effective across all four indicators. “Telling” is characterized by the female leader providing clear and structured guidance through written and verbal instructions tailored to the type of task. “Selling” demonstrates the leader’s use of open, two-way communication by involving and valuing employees’ opinions. Participating is seen in the active involvement between the female leader and employees in decision-making and strengthening cooperation. Delegating is demonstrated by placing high trust in employees to work independently, with the leader focusing on evaluating the final results.